Pergeseran Tradisi Pemujaan Leluhur Dalam Hubungan dengan Organisasi Ruang Rumah Tionghoa Saat Ini di Surabaya - Lintu Tulistyantoro, Priscillia Sasmita (Intra, 2014)
Chinese people is the most immigrants around the world compared to the others. Although they lived with so many people around the world, they kept do their tradition with respect to their anchestor. Surabaya known as coastal settlements so that a lot of immigrants will come, include Chinese people. One of the Chinese tradition is Anchestor Worship. Chinese people who do this tradition usually has a anchestor worshipâs altar in their house. Anchestor worshipâs altar has a big influence in organization of space, because it has a lot of rules to organize. This research use the qualitatif method which is descriptive in character. The result of this research show that a lot of difference between the literature and the fact, that achestor worshipâs altar didnât give influence to chinese house anymore. It can because of so many factor, such as environmental condition or chinese people who forget their tradition.